Lagrangian eddy kinetic energy of ocean mesoscale eddies and its application to the Northwestern Pacific - Ding, Mengrong; Lin, Pengfei; Liu, Hailong; Hu, Aixue; Liu, Chuanyu (Scientific reports, 2020)
Coherent oceanic mesoscale eddies with unique dynamical structures have great impacts on ocean transports and global climate. Eddy kinetic energy (EKE), derived from time-dependent circulation, is commonly used to study mesoscale eddies. However, there are three deficiencies of EKE when focusing on the analysis of coherent mesoscale eddies. Here, we propose a comprehensive concept—Lagrangian EKE (LEKE) as an additional metric which is a combination of gridded EKE calculated in Eulerian framework and tracked coherent mesoscale eddies in Lagrangian framework. Evidences suggest that LEKE can make up these deficiencies as an effective supplement. In this study, regional application over Northwestern Pacific Ocean is taken as an example. It clearly demonstrates that LEKE reveals more accurate and detailed characteristics of both cyclonic and anticyclonic eddies than EKE when coherent mesoscale eddies are the specific focus, such as the variation rates of kinetic energy during the eddy propagation, spatial–temporal differences of kinetic energy between cyclonic and anticyclonic eddies. Overall, using LEKE to analyze coherent mesoscale eddies gives the rise to understand the spatial–temporal contrasts between eddies with different polarities, and provides a new perspective to recognize the crucial role played by coherent mesoscale eddies in the ocean.